Urban resilience & climate change - Anwar, Farhan (Karachi, 2013)
This book explores the concept of urban resilience in the face of climate change. It addresses the challenges cities are facing due to increasing temperatures, extreme weather events, and rising sea levels, and provides strategies for building resilience in urban areas. The authors discuss the importance of incorporating climate change adaptation and mitigation measures into urban planning and provide case studies of cities that are taking proactive steps to become more resilient.
Keywords: Urban resilience; Climate change; Mitigation; Adaptation